Student midwives' experiences of high-fidelity simulation in midwifery education in the university setting: A qualitative systematic review - Jolly, Louise; Ooms, Ann; Ransome, Hazel (Nurse education today, 2025)
High- Fidelity Simulation is an increasingly popular, evidence-based, and technologically sophisticated pedagogical approach within nursing and midwifery education and simulated practice learning. Various systematic reviews exploring the effectiveness of High- Fidelity Simulation have been undertaken, yet there is limited evidence and no current systematic review about student midwives' experiences of High- Fidelity Simulation. Due to this lack of evidence, the proposed review into student midwives' experiences of High- Fidelity Simulation is highly justified. This review aims to provide new insights into this pedagogical approach within midwifery education and shape recommendations to assist midwifery educators to deliver high-quality High-Fidelity Simulation. To explore what is known about the experiences of student midwives who have engaged in High- Fidelity Simulation as part of their midwifery education within the university setting. The Joanna Briggs Institute (JBI) methodology for qualitative systematic reviews was followed and the study is reported using the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) guidelines. The review found High- Fidelity Simulation to be a beneficial learning process, however some negative experiences were also identified. Two main themes emerged related to barriers and facilitators. Facilitators included the following seven subthemes: practical skill development, authenticity of the manikin and surroundings, application of theory to practice, increased confidence, practicing in a safe learning environment, improved team working skills, and the value of feedback. Barriers included the following 5 subthemes: a lack of realism, stress and pressure whilst role playing, anxiety, feelings of guilt, shame and decreased self-esteem, and group allocation. Overall, the synthesized findings highlight that student midwives perceive the use of High- Fidelity Simulation to be highly beneficial, positively impacting their clinical competence and team working skills. Moreover, if High- Fidelity Simulation was used consistently and alongside adequate preparation and debriefing processes any unnecessary emotional harm could be avoided. Therefore, the application of High-Fidelity Simulation has the potential to develop a midwifery workforce that is better equipped to practice safely and more effectively at the point of registration, which could reduce mortality and morbidity rates for women and babies. •High Fidelity Simulation•Enables student midwives to learn from mistakes in a safe environment•Positive impact on student midwives' clinical competence and confidence levels•Effectively facilitates the application of theory to practice•Improved team working skills through real life scenarios and role play